IEEE Photonic Society 24th Annual Meeting 2011
DOI: 10.1109/pho.2011.6110797
|View full text |Cite
|
Sign up to set email alerts
|

Spatial light interference microscopy (SLIM)

Abstract: Abstract:We present spatial light interference microscopy (SLIM) as a new optical microscopy technique, capable of measuring nanoscale structures and dynamics in live cells via interferometry. SLIM combines two classic ideas in light imaging: Zernike's phase contrast microscopy, which renders high contrast intensity images of transparent specimens, and Gabor's holography, where the phase information from the object is recorded. Thus, SLIM reveals the intrinsic contrast of cell structures and, in addition, rend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This effect is also present in transport of intensity experiments that share similar experimental conditions (i.e. sample-camera distance < 900μm) [29,30] and other quantitative phase imaging techniques [31,32]. However, lensless phase imagers are mainly used to image biological samples like cells [4][5][6][7][8][9][10] which sizes are typically less than 20μm for which the phase can be correctly computed.…”
Section: Phase Recoverymentioning
confidence: 99%
“…This effect is also present in transport of intensity experiments that share similar experimental conditions (i.e. sample-camera distance < 900μm) [29,30] and other quantitative phase imaging techniques [31,32]. However, lensless phase imagers are mainly used to image biological samples like cells [4][5][6][7][8][9][10] which sizes are typically less than 20μm for which the phase can be correctly computed.…”
Section: Phase Recoverymentioning
confidence: 99%
“…The retrieved method can be found in previous reports. 9 The irradiance distribution at each point r ¼ ðx; yÞ in the image plane is a function of the phase shift, namely E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 1 ; 6 3 ; 5 9 4…”
Section: Image Processingmentioning
confidence: 99%
“…QPI is an emerging method that provides quantitative information about transparent specimens, with nanoscale sensitivity and in label-free mode. 9 Various implementations of QPI have been used recently to study the topography of gametes, assuming a certain refractive index. [10][11][12][13][14][15][16] Rappaz et al 17 reported an experimental procedure to calculate both the refractive index and the cellular thickness from the phase shift using digital holographic microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In previous TPM experimental arrangements (Fang‐Yen et al ., ; Popescu, ; Xiu et al ., ), the angle of the reference beam incident into the image plane was fixed. Taking the numerical aperture (NA) and the pixel size of the camera into consideration, the maximum resolvable phase gradient will be reduced.…”
Section: Introductionmentioning
confidence: 99%